2009
DOI: 10.1093/nar/gkp1128
|View full text |Cite
|
Sign up to set email alerts
|

Auxin regulation of the microRNA390-dependent transacting small interfering RNA pathway in Arabidopsis lateral root development

Abstract: MicroRNA (miR)390 cleaves the non-coding TAS3 precursor RNA for the production of tasiRNA-ARF, a group of an endogenous trans-acting small-interfering RNAs which cleave the transcripts of auxin response factor (ARF) 3/4. miR390-cleaved TAS3 RNA is polymerized and diced into tasiRNA-ARF by RNA-dependent RNA polymerase6 (RDR6) and Dicer-like4 (DCL4), respectively. tasiRNA-ARF-dependent post-transcriptional gene silencing (PTGS) of ARF3/4 is involved in auxin-mediated polarity establishment in the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(155 citation statements)
references
References 46 publications
5
148
1
1
Order By: Relevance
“…Our results demonstrate that the control exerted by auxin on lateral root initiation is at least bimodal and consists of the crucial early SLR/IAA14-ARF7-ARF19-dependent auxin response module (3-7, 23, 24), followed by a second BDL/ IAA12-MP/ARF5-dependent module. Most likely, more modules are involved, because other ARFs have been implicated in adventitious and lateral root development (3,(29)(30)(31)(32)(33)(34). We propose that discrete auxin response modules successively coordinate distinct developmental processes, most probably through the regulation of unique targets, comparable to the spatially distinct, bipartite auxin response during hypophysis specification (19).…”
Section: Resultsmentioning
confidence: 92%
“…Our results demonstrate that the control exerted by auxin on lateral root initiation is at least bimodal and consists of the crucial early SLR/IAA14-ARF7-ARF19-dependent auxin response module (3-7, 23, 24), followed by a second BDL/ IAA12-MP/ARF5-dependent module. Most likely, more modules are involved, because other ARFs have been implicated in adventitious and lateral root development (3,(29)(30)(31)(32)(33)(34). We propose that discrete auxin response modules successively coordinate distinct developmental processes, most probably through the regulation of unique targets, comparable to the spatially distinct, bipartite auxin response during hypophysis specification (19).…”
Section: Resultsmentioning
confidence: 92%
“…10 It is known that the auxin responsive factor 4 (ARF4) positively regulates lateral root formation and its transcript is targeted by ta-siRNA-ARF. 8 It is unclear how much the enhanced silencing of ARF4 could contribute to the lateral root phenotype of fry1, because the generation of ta-siRNA-ARF from TAS3 depends on the intact function of RNAdependent RNA polymerase RDR6, and the rdr6 mutant has fewer lateral roots than wild type. 8 Moreover, in our study, RT-PCR analysis did not detect a clear difference in ARF2 or ARF4 transcript levels between the wild-types and fry1 mutants (data not shown).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…The genetic interaction between HY5 and FRY1 indicates that HY5 and FRY1 may act in overlapping pathways that mediate light signaling and lateral root development. 1,4-6 Among them, several miRNA and target mRNA pairs, including miR164 and NAC1, 7 tasiRNA-ARF and ARF4, 8 and miR160 and ARF17, 9 have been shown to be involved in lateral root development. In a recent study, 10 we reported that the bifunctional enzyme FRY1 controls lateral root architecture through suppression of RNA silencing.…”
mentioning
confidence: 99%
“…miR165/166 and miR319 regulate leaf development and morphogenesis by targeting gene transcripts encoding HD-ZIP and TCP transcription factors, respectively Rhoades et al, 2002;Palatnik et al, 2003;Tang et al, 2003;Juarez et al, 2004). miR160, miR167, and miR390 play roles in root and lateral root development, as well as embryo, leaf, and floral organ development, by targeting transcripts of Auxin Response Factor10 (ARF10)/ARF16/ARF17, ARF6/ARF8, and ARF2/ARF3/ARF4 genes, respectively (Mallory et al, 2005;Wang et al, 2005;Wu et al, 2006;Gutierrez et al, 2009;Liu et al, 2010;Marin et al, 2010;Yoon et al, 2010). While miR160 and miR167 directly target their ARF transcripts, miR390 targets Trans-Acting siRNA3 to trigger the biogenesis of trans-acting small interfering RNAs, which subsequently inhibit ARF2/ARF3/ARF4 to release the repression of lateral root growth (Marin et al, 2010;Yoon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%